2021
DOI: 10.2139/ssrn.3855959
|View full text |Cite
|
Sign up to set email alerts
|

Employers' Willingness to Invest in the Training of Temporary Workers: A Discrete Choice Experiment

Abstract: Employers' willingness to invest in the training of temporary workers: a discrete choice experiment*Various studies have shown that temporary workers participate less in training than those on permanent contracts. Human resources practices are considered to be an important explanation for this difference. We develop a theoretical framework for employers' provision of training that explicitly incorporates the costs and benefits associated with training investments in employees with different types of employment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…Each additional job change in the previous five years decreases the chances a job candidate is selected for training by around 6.5 percentage points. This is consistent with recent evidence that Dutch managers are less willing to train workers in temporary contracts, especially if they are unlikely to have an ongoing attachment to the firm in the future(Poulissen et al, 2021). Decision makers are also morereluctant to choose training options involving general rather than specific training.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Each additional job change in the previous five years decreases the chances a job candidate is selected for training by around 6.5 percentage points. This is consistent with recent evidence that Dutch managers are less willing to train workers in temporary contracts, especially if they are unlikely to have an ongoing attachment to the firm in the future(Poulissen et al, 2021). Decision makers are also morereluctant to choose training options involving general rather than specific training.…”
supporting
confidence: 87%
“…One key advantage of our data is that they provide information about managers' personality traits and economic preferences. Previous vignette studies of worker training have either focused solely on the attributes of training scenarios themselves (see Fleischmann and Koster, 2017;Poulissen et al, 2021) or accounted only for managers' age, education, and organizational position (Karpinska et al, 2015). Our data include among other things, measures of locus of control, Big-5 personality traits, patience, and, most importantly for our analysis, attitudes towards risk.…”
Section: Estimation Samplementioning
confidence: 99%
“…Researchers have concluded that organizations do not invest in training temporary employees, regardless of how much they identify with their client organizations (Manelkar et al ., 2023; Bosmans et al ., 2016). Due to the temporary nature of their jobs, TPEs do not guarantee commitment which acts as a barrier to their training (Poulissen et al ., 2021). In other words, their payback period for the investment is low (Fugate et al ., 2021) due to frequent shift in organizations, for better projects.…”
Section: Introductionmentioning
confidence: 99%